Planosol soil sample size for computerized tomography measurement of physical parameters - Alceu Pedrotti; Eloy Antonio Pauletto; Silvio Crestana; Paulo Estevão Cruvinel; Carlos Manoel Pedro Vaz; João de Mendonça Naime; Alvaro Macedo da Silva (Scientia Agricola, 2003)
Computerized tomography (CT) is an important tool in Soil Science for noninvasive measurement of density and water content of soil samples. This work aims to describe the aspects of sample size adequacy for Planosol (Albaqualf) and to evaluate procedures for statistical analysis, using a CT scanner with a 241Am source. Density errors attributed to the equipment are 0.051 and 0.046 Mg m-3 for horizons A and B, respectively. The theoretical value for sample thickness for the Planosol, using this equipment, is 4.0 cm for the horizons A and B. The ideal thickness of samples is approximately 6.0 cm, being smaller for samples of the horizon B in relation to A. Alternatives for the improvement of the efficiency analysis and the reliability of the results obtained by CT are also discussed, and indicate good precision and adaptability of the application of this technology in Planosol (Albaqualf) studies.